Pengaruh Pemberian Tes Lisan Sebelum Pembelajaran terhadap Pencapaian Hasil Belajar Bahasa Inggris Mahasiswa Program Studi Pendidikan Agama Islam STIT Palapa Nusantara Lombok - Jumatriadi, Jumatriadi (Lembaga Yasin AlSys, 2023)
This research aims to investigate the influence of administering an oral test before learning on the achievement of English language learning outcomes among students at STIT Palapa Nusantara Lombok. In the teaching and learning process, administering an oral test before learning can have benefits such as enhancing learning motivation, stimulating mental preparation, and identifying students' learning deficiencies and needs. The method used in this research is an experimental method with a Posttest-Only Control Design. The study was conducted on students of the Islamic Education Study Program in the even semester of the academic year 2022/2023 at STIT Palapa Nusantara Lombok. The experimental group received treatment in the form of an English oral test before learning, while the control group did not receive this treatment. Data were obtained through the oral test before learning and the learning outcome test (final test) given to both groups. Data analysis was performed using instrument validity and reliability tests, descriptive statistics, normality test, homogeneity test, and mean difference test. The data description results showed different average values between the experimental group and the control group. The statistical analysis showed that administering an oral test before learning has a significant influence on the achievement of English language learning outcomes among students at STIT Palapa Nusantara Lombok. This research is expected to provide a better understanding of the influence of administering an oral test before learning on the achievement of English language learning outcomes among students. The results of this research can serve as a reference in the development of effective English language learning strategies at STIT Palapa Nusantara Lombok and other higher education institutions.